Integrating Skouw Local Wisdom into Deep Learning–Based Science Instruction to Foster Elementary Students’ Critical Thinking - Kusdianto, Kusdianto; Budiarti, Indah Slamet; Endriani, Endriani; Wati, Lely Yustina (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study analyzes the local wisdom of the Skouw community in Muara Tami District, Jayapura City, as a contextual science learning resource to stimulate elementary school students’ critical thinking skills through a deep learning approach. Motivated by the scarcity of culturally relevant learning resources in elementary science education—particularly in communities with rich indigenous ecological knowledge—this investigation employed a qualitative exploratory case study design complemented by a development-oriented stage. Data were collected through observations, semi-structured interviews, and document analysis involving school principals, science teachers, and selected elementary school students, as well as school documents and contextual community observations. Analysis followed a systematic procedure comprising data reduction, coding, data display, thematic interpretation, and conclusion verification, with trustworthiness ensured through source triangulation, method triangulation, and member checking. The findings indicate that Skouw local wisdom—encompassing environmental knowledge, traditional agricultural practices, simple technology, customary resource management, and cultural values—can be meaningfully connected with elementary science concepts such as ecosystems, biodiversity, conservation, adaptation, energy, simple machines, and human–environment interaction. Implementation of local wisdom-based science learning encouraged students to relate scientific concepts to real-life cultural and ecological experiences, participate more actively, and develop reflective and analytical thinking. However, challenges related to limited contextual learning resources, teachers’ competence, school–community collaboration, and learning facilities were also identified. The study implies that culturally grounded science learning can provide an alternative pedagogical framework for contextual, meaningful, and identity-based science education, while supporting teachers in designing activities that stimulate critical thinking through local cultural resources.